Implementing a psychosocial care approach in pediatric inpatient care: process evaluation of the pilot Child Life Specialist program at the University Hospital of Munich, Germany - Hummel, Julia; Voss, Stephan; Clark, Holly; Coenen, Michaela; Klein, Christoph; Rehfuess, Eva A.; Zu Rhein, Valerie; Voigt-Blaurock, Varinka; Jung-Sievers, Caroline (Frontiers in Pediatrics, 2023)
Background: Child Life Specialists (CLSs) are psychosocial care professionals of child development and health who focus on the individual needs and rights of young patients. CLSs accompany sick children and focus on the children’s perspective and their reality of life. CLS programs are already established in clinical settings in the United States and other Anglophone countries but have not yet been piloted in the German health care setting, neither has their implementation been evaluated in this context. This study aimed to explore the factors influencing the implementation of a pilot CLS program in pediatric inpatient care at the Dr. von Hauner Children’s Hospital at the University Hospital of Munich, Germany. Methods: Building on methods commonly employed in the evaluation of complex interventions, we developed a logic model to guide the process evaluation of our program. Semi-structured interviews with four groups of stakeholders were conducted in person or via videoconferencing between June 2021 and January 2022. Data was analyzed collectively using the method of qualitative content analysis by Mayring. Results: Fifteen individual interviews were conducted with patients (children aged 5-17 years, n=4), parents (n=4), CLSs (n=4) and other health professionals (n=3). Factors influencing the implementation were identified on three levels: system, staff and intervention. On the system level, a clearer definition of CLSs’ tasks and responsibilities was perceived as important and would likely lead to a delineation from other (psychosocial) professions and a reduction of potential resistances. On the staff level, lacking training opportunities and feelings of being insufficiently skilled were limiting the CLSs professional self-confidence. On the intervention level, the emergence of a unique characteristic of the CLSs’ work (i.e., preparation for medical procedures) supported the acceptance of the new program. Conclusions: The implementation of a CLS program into an established hospital system with existing psychosocial care services is challenging. Our results contribute to a better understanding of implementation processes of such an additional psychosocial care approach and provide recommendations for addressing upcoming challenges.